High-strength energy-saving emission-reducing recycled concrete and preparation method thereof

By preparing to enhance fillers and combined with recycled aggregate and cement materials, the problem of low regenerative concrete performance has been solved, it significantly improves pressure resistance and folding strength, and achieves high intensity and energy saving and emission reduction effects.

CN119371160APending Publication Date: 2025-01-28NANTONG ARTHUR CONSTRUCTION ENGINEERING CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411484255.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The mechanical properties of existing recycled concrete are low, mainly due to the excessive edges and angles of recycled aggregates, high water absorption, large porosity and low apparent density.

Method used

By preparing enhancement, including adding polyacrylamide, carbide silicone, magnesium and steel fiber to the silicone solution, and the ball grinding to obtain enhanced fillers, combined with recycled rough aggregate, regenerative fine aggregate and cement to improve the regenerative bone The interface of the material is binding and the gap rate.

Benefits of technology

It significantly improves the mechanical properties of recycled concrete, including pressure resistance and reflective strength, reaching 54.6 mPa and 10.8 MPA, which is much higher than traditional regenerative concrete.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to high-strength energy-saving emission-reducing recycled concrete and a preparation method thereof. The recycled concrete comprises the following components in parts by weight: 1000 parts of recycled coarse aggregate, 600-800 parts of recycled fine aggregate, 200-400 parts of cement, 50-200 parts of reinforcing filler, 0.5-20 parts of a water reducing agent, 0.5-20 parts of a thickening agent, 0-2 parts of a retarder and 150-250 parts of water, the recycled coarse aggregate is prepared from waste concrete through the steps of cleaning, crushing and sorting; the recycled fine aggregate is composed of waste glass yarn and waste marble in a mass ratio of (50-70): (30-50); the reinforcing filler is prepared by the following steps: sequentially adding polyacrylamide and silicon carbide whiskers into silica sol, stirring, sequentially adding magnesium oxide and steel fibers, and carrying out ball milling to obtain the reinforcing filler. Compared with the prior art, the concrete provided by the invention has excellent compression resistance and fracture resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of concrete, and in particular to a high-strength energy-saving and emission-reducing recycled concrete and a preparation method thereof. Background Art

[0002] Concrete has the characteristics of abundant raw materials, low price and simple production process, so its usage is increasing. At the same time, concrete also has the characteristics of high compressive strength, good durability and wide range of strength grades. These characteristics make it widely used. It is not only used in various civil engineering projects, but also in shipbuilding, machinery industry, marine development, geothermal engineering, etc. Concrete is also an important material.

[0003] And with the development of the economy, various infrastructures are constantly demolished and rebuilt, generating a large amount of construction waste, of which the proportion that can be recycled is too small. Most of the construction waste is dumped or landfilled, which not only occupies arable land, but also pollutes the environment.

[0004] Recycled concrete is a new type of concrete made by crushing, screening, and removing impurities from waste concrete blocks to prepare recycled aggregates, which partially or completely replace natural aggregates. Recycled aggregate technology can not only solve the problem of construction waste occupying arable land and polluting the environment from the source, but also make up for the huge demand for natural sand and gravel in infrastructure construction, promote the recycling of waste concrete, and thus achieve sustainable development of resources, environment, and ecology.

[0005] For example, CN112811869B discloses a concrete and its preparation method and use. The concrete includes recycled coarse aggregate, waste glass sand, cement, polycarboxylic acid water reducer, talcum powder, and thermal insulation filler; the preparation method of the thermal insulation filler is: after the silicon aerogel powder is subjected to plasma surface treatment, it is evenly divided into multiple portions and mixed with asbestos fibers and silicon carbide whiskers, so that the silicon aerogel powder is fully dispersed in the asbestos fiber and silicon carbide whisker dry powder mixture, and is wrapped by the three-dimensional structure of the asbestos fiber and silicon carbide whisker, having a special spatial structure, and enhancing the thermal insulation performance of the silicon aerogel powder.

[0006] For example, CN117088630A discloses a recycled concrete admixture, recycled concrete and a preparation method thereof, wherein the recycled concrete admixture comprises calcined hydrotalcite; the calcined hydrotalcite is obtained by calcining hydrotalcite at a temperature below 600°C, wherein after calcining the hydrotalcite at an appropriate temperature, the hydrotalcite loses its interlayer anions and moisture to obtain calcined hydrotalcite.

[0007] However, the recycled concrete aggregates obtained after crushing waste concrete and discarded bricks have too many edges and corners, and most of the recycled aggregates are needle-shaped. In addition, tiny cracks will appear inside the aggregates during the crushing process of the recycled aggregates. At the same time, a part of the old mortar is generally adhered to the surface of the recycled aggregates. Compared with natural aggregates, the recycled aggregates have the characteristics of large crushing index, high water absorption rate, large porosity, and low apparent density, which makes the mechanical properties of recycled concrete relatively low.

[0008] Based on this, the present invention is proposed. Summary of the invention

[0009] The purpose of the present invention is to provide a high-strength energy-saving and emission-reducing recycled concrete and a preparation method thereof in order to overcome the low mechanical properties of the above-mentioned prior art.

[0010] The purpose of the present invention can be achieved by the following technical solutions:

[0011] The present invention provides a high-strength energy-saving and emission-reducing recycled concrete, comprising the following components by weight: 1000 parts of recycled coarse aggregate, 600-800 parts of recycled fine aggregate, 200-400 parts of cement, 50-200 parts of reinforcing filler, 0.5-20 parts of water reducer, 0.5-20 parts of thickener, 0-2 parts of retarder, and 150-250 parts of water;

[0012] The recycled coarse aggregate is made from waste concrete through the steps of cleaning, crushing and sorting;

[0013] The recycled fine aggregate is composed of waste glass yarn and waste marble in a mass ratio of (50-70): (30-50);

[0014] The reinforcing filler is prepared in the following manner:

[0015] Polyacrylamide and silicon carbide whiskers are sequentially added to the silica sol, and magnesium oxide and steel fiber are sequentially added after stirring, and the reinforcing filler is obtained after ball milling.

[0016] Preferably, the mass ratio of the silica sol, silicon carbide whisker, magnesium oxide, steel fiber and polyacrylamide is 100:(5-15):(30-50):(30-50)(5-10);

[0017] And / or, the stirring time is 4-8h;

[0018] And / or, the ball milling time is 15-45 min, and the ball milling speed is 100-200 r / min;

[0019] And / or, the length of the silicon carbide whisker is 10-50 μm, the diameter is 0.1-0.6 μm, and the particle size of the magnesium oxide is 50-100 nm.

[0020] Preferably, the particle size of the recycled coarse aggregate is 5-10 mm, and the particle size of the recycled fine aggregate is 0.25-0.5 mm.

[0021] Preferably, the water reducer is a polycarboxylate water reducer;

[0022] And / or, the thickener is nanoclay;

[0023] and / or, the retarder is one or more of sodium gluconate, citric acid, or sodium citrate, preferably sodium gluconate;

[0024] And / or, the cement is ordinary Portland cement PO42.5.

[0025] The present invention also provides a method for preparing high-strength energy-saving and emission-reducing recycled concrete, comprising the following steps:

[0026] S1, adding polyacrylamide and silicon carbide whiskers to silica sol in sequence, adding magnesium oxide and steel fiber in sequence after stirring, and obtaining reinforcing filler after ball milling;

[0027] S2, mixing recycled coarse aggregate, recycled fine aggregate, cement, water reducer, thickener, retarder and water until they are evenly mixed, then adding reinforcing filler, mixing evenly, and naturally curing to obtain high-strength energy-saving and emission-reducing recycled concrete;

[0028] Wherein, the recycled coarse aggregate is made from waste concrete through the steps of cleaning, crushing and sorting;

[0029] The recycled fine aggregate consists of waste glass yarn and waste marble in a mass ratio of (50-70):(30-50).

[0030] Preferably, in step S1, the mass ratio of the silica sol, silicon carbide whiskers, magnesium oxide, steel fiber and polyacrylamide is 100:(5-15):(30-50):(30-50)(5-10);

[0031] And / or, in step S1, the stirring time is 4-8h;

[0032] And / or, in step S1, the ball milling time is 15-45 min, and the ball milling speed is 100-200 r / min;

[0033] And / or, in step S1, the length of the silicon carbide whisker is 10-50 μm, the diameter is 0.1-0.6 μm, and the particle size of the magnesium oxide is 50-100 nm.

[0034] Preferably, the mass ratio of the recycled coarse aggregate, recycled fine aggregate, cement, reinforcing filler, water reducer, thickener, retarder and water is 1000:(600-800):(200-400):(50-200):(0.5-20):(0-2):(150-250).

[0035] Preferably, in step S2, the particle size of the recycled coarse aggregate is 5-10 mm, and the particle size of the recycled fine aggregate is 0.25-0.5 mm.

[0036] Preferably, in step S2, the water reducer is a polycarboxylate water reducer;

[0037] And / or, in step S2, the thickener is nanoclay;

[0038] and / or, in step S2, the retarder is one or more of sodium gluconate, citric acid, or sodium citrate, preferably sodium gluconate;

[0039] And / or, in step S2, the cement is ordinary Portland cement PO42.5.

[0040] The present invention further provides a recycled concrete obtained by the method for preparing the high-strength, energy-saving and emission-reducing recycled concrete as described above.

[0041] Compared with the prior art, the present invention has the following beneficial effects:

[0042] The present invention improves the mechanical properties of recycled concrete by enhancing the void ratio of recycled aggregates filled with fillers and improving the interface bonding between recycled aggregates.

[0043] Among them, silicon carbide whiskers are first dispersed in silica sol through polyacrylamide. This is mainly because the polyacrylamide adsorbed on the surface of silicon carbide whiskers forms an adsorption layer of a certain thickness, which effectively prevents silicon carbide whiskers from agglomerating through van der Waals forces. This pre-dispersion effect prevents silicon carbide whiskers from agglomerating and enables silicon carbide whiskers to be well dispersed in concrete. Secondly, magnesium oxide and steel fibers are added. Magnesium oxide is combined with silicon carbide whiskers through the bonding effect of silica sol. Steel fibers are used to fill the interface between silicon carbide whiskers and recycled aggregates or the interface between magnesium oxide and recycled aggregates, thereby enhancing the compactness of the interface. When forming concrete, magnesium oxide can react with water to generate magnesium hydroxide and form a dense gel in the concrete. This gel further fills the pores between the recycled aggregates and reacts chemically with the cement stone matrix to form a relatively stable crystalline product. At this time, the steel fibers are solidified on the interface, thereby further enhancing the mechanical properties of the concrete. The mechanical properties of the concrete are synergistically improved by the gap filling effect of silicon carbide whiskers and the curing effect of magnesium oxide.

[0044] Furthermore, the use of recycled coarse aggregate and recycled fine aggregate achieves the effect of energy conservation and emission reduction, and in the recycled fine aggregate, marble can also improve the fluidity of waste glass yarn, further making the recycled coarse aggregate and recycled fine aggregate mixed evenly. DETAILED DESCRIPTION

[0045] For ease of understanding of the present application, the present application will be described more fully below by way of embodiments. However, the present application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present application more thorough and comprehensive.

[0046] For simplicity, this application only explicitly discloses some numerical ranges. However, any lower limit can be combined with any upper limit to form an unclearly recorded range; and any lower limit can be combined with other lower limits to form an unclearly recorded range, and any upper limit can be combined with any other upper limit to form an unclearly recorded range. In addition, although not clearly recorded, each point or single value between the range endpoints is included in the range. Thus, each point or single value can be combined with any other point or single value as its own lower limit or upper limit or with other lower limits or upper limits to form an unclearly recorded range.

[0047] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art in the technical field of the present application. The terms used herein in the specification of the present application are only for the purpose of describing specific embodiments and are not intended to limit the present application. It should be noted that, unless otherwise specified, the term "and / or" used herein includes any and all combinations of one or more related listed items, and "above" and "below" include the number, and the meaning of "multiple" in "one or more" is more than two.

[0048] The recycled concrete aggregate obtained after crushing waste concrete and discarded bricks has too many edges and corners, and most of the recycled aggregates are needle-shaped. In the process of crushing the recycled aggregates, tiny cracks will appear inside the aggregates. At the same time, a part of the old mortar is generally adhered to the surface of the recycled aggregates. Compared with natural aggregates, the recycled aggregates have the characteristics of large crushing index, high water absorption rate, large porosity, low apparent density, etc., which makes the mechanical properties of recycled concrete relatively low.

[0049] Based on this, the first aspect of the embodiment of the present application provides a high-strength energy-saving and emission-reducing recycled concrete, comprising the following components by weight: 1000 parts of recycled coarse aggregate, 600-800 parts of recycled fine aggregate, 200-400 parts of cement, 50-200 parts of reinforcing filler, 0.5-20 parts of water reducer, 0.5-20 parts of thickener, 0-2 parts of retarder, and 150-250 parts of water;

[0050] The recycled coarse aggregate is made from waste concrete through the steps of cleaning, crushing and sorting;

[0051] The recycled fine aggregate is composed of waste glass yarn and waste marble in a mass ratio of (50-70): (30-50);

[0052] The reinforcing filler is prepared in the following manner:

[0053] Polyacrylamide and silicon carbide whiskers are sequentially added to the silica sol, and magnesium oxide and steel fiber are sequentially added after stirring, and the reinforcing filler is obtained after ball milling.

[0054] In an optional embodiment, the mass ratio of the silica sol, silicon carbide whiskers, magnesium oxide, steel fiber and polyacrylamide is 100:(5-15):(30-50):(30-50)(5-10).

[0055] In an optional embodiment, the mass ratio of the silica sol, silicon carbide whiskers, magnesium oxide and steel fiber is 100:10:40:40.

[0056] In an optional embodiment, the stirring time is 4-8 hours.

[0057] In an optional embodiment, the stirring time is 6 hours.

[0058] In an optional implementation manner, the ball milling time is 15-45 min, and the ball milling speed is 100-200 r / min.

[0059] In an optional embodiment, the length of the silicon carbide whisker is 10-50 μm, the diameter is 0.1-0.6 μm, and the particle size of the magnesium oxide is 50-100 nm.

[0060] The present invention improves the mechanical properties of recycled concrete by enhancing the void ratio of recycled aggregates filled with fillers and improving the interface bonding between recycled aggregates.

[0061] Among them, silicon carbide whiskers are first dispersed in silica sol through polyacrylamide. This is mainly because the polyacrylamide adsorbed on the surface of silicon carbide whiskers forms an adsorption layer of a certain thickness, which effectively prevents silicon carbide whiskers from agglomerating through van der Waals forces. This pre-dispersion effect prevents silicon carbide whiskers from agglomerating and enables silicon carbide whiskers to be well dispersed in concrete. Secondly, magnesium oxide and steel fibers are added. Magnesium oxide is combined with silicon carbide whiskers through the bonding effect of silica sol. Steel fibers are used to fill the interface between silicon carbide whiskers and recycled aggregates or the interface between magnesium oxide and recycled aggregates, thereby enhancing the compactness of the interface. When forming concrete, magnesium oxide can react with water to generate magnesium hydroxide and form a dense gel in the concrete. This gel further fills the pores between the recycled aggregates and reacts chemically with the cement stone matrix to form a relatively stable crystalline product. At this time, the steel fibers are solidified on the interface, thereby further enhancing the mechanical properties of the concrete. The mechanical properties of the concrete are synergistically improved by the gap filling effect of silicon carbide whiskers and the curing effect of magnesium oxide.

[0062] In an optional embodiment, the particle size of the recycled coarse aggregate is 5-10 mm, and the particle size of the recycled fine aggregate is 0.25-0.5 mm.

[0063] In an optional embodiment, the water reducer is a polycarboxylate water reducer.

[0064] In an optional embodiment, the thickener is nanoclay.

[0065] In an optional embodiment, the retarder is one or more of sodium gluconate, citric acid, or sodium citrate, preferably sodium gluconate.

[0066] In an optional embodiment, the cement is ordinary Portland cement PO42.5.

[0067] The second aspect of the embodiment of the present application provides a method for preparing high-strength energy-saving and emission-reducing recycled concrete, comprising the following steps:

[0068] S1, adding polyacrylamide and silicon carbide whiskers to silica sol in sequence, adding magnesium oxide and steel fiber in sequence after stirring, and obtaining reinforcing filler after ball milling;

[0069] S2, mixing recycled coarse aggregate, recycled fine aggregate, cement, water reducer, thickener, retarder and water until they are evenly mixed, then adding reinforcing filler, mixing evenly, and naturally curing to obtain high-strength energy-saving and emission-reducing recycled concrete;

[0070] Wherein, the recycled coarse aggregate is made from waste concrete through the steps of cleaning, crushing and sorting;

[0071] The recycled fine aggregate consists of waste glass yarn and waste marble in a mass ratio of (50-70):(30-50).

[0072] In an optional embodiment, in step S1, the mass ratio of the silica sol, silicon carbide whiskers, magnesium oxide, steel fiber and polyacrylamide is 100:(5-15):(30-50):(30-50)(5-10).

[0073] In an optional embodiment, in step S1, the mass ratio of the silica sol, silicon carbide whiskers, magnesium oxide and steel fiber is 100:10:40:40.

[0074] In an optional embodiment, in step S1, the stirring time is 4-8 hours.

[0075] In an optional embodiment, in step S1, the stirring time is 6 hours.

[0076] In an optional embodiment, in step S1, the ball milling time is 15-45 min, and the ball milling speed is 100-200 r / min.

[0077] In an optional embodiment, in step S1, the length of the silicon carbide whisker is 10-50 μm, the diameter is 0.1-0.6 μm, and the particle size of the magnesium oxide is 50-100 nm.

[0078] In an optional embodiment, in step S2, the mass ratio of the recycled coarse aggregate, recycled fine aggregate, cement, reinforcing filler, water reducer, thickener, retarder and water is 1000:(600-800):(200-400):(50-200):(0.5-20):(0-2):(150-250).

[0079] In an optional embodiment, in step S2, the particle size of the recycled coarse aggregate is 5-10 mm, and the particle size of the recycled fine aggregate is 0.25-0.5 mm.

[0080] In an optional embodiment, in step S2, the water reducer is a polycarboxylate water reducer.

[0081] In an optional embodiment, in step S2, the thickener is nanoclay.

[0082] In an optional embodiment, in step S2, the retarder is one or more of sodium gluconate, citric acid, or sodium citrate, preferably sodium gluconate.

[0083] In an optional embodiment, in step S2, the cement is ordinary Portland cement PO42.5.

[0084] The above implementation is described in more detail below in conjunction with specific examples.

[0085] Example 1

[0086] This embodiment provides a method for preparing high-strength energy-saving and emission-reducing recycled concrete, comprising the following steps:

[0087] S1, adding polyacrylamide and silicon carbide whiskers to silica sol in sequence, stirring and then adding magnesium oxide and steel fiber in sequence, wherein the mass ratio of silica sol, silicon carbide whiskers, magnesium oxide, steel fiber and polyacrylamide is 100:10:40:40:8, and then ball milling at a speed of 150 r / min for 30 min to obtain a reinforcing filler;

[0088] S2, 1000 parts of recycled coarse aggregate with a particle size of 10 mm, 490 parts of waste glass yarn with a particle size of 0.25 mm, 210 parts of waste marble with a particle size of 0.5 mm, 250 parts of ordinary Portland cement PO42.5, 10 parts of polycarboxylate water reducer, 10 parts of nanoclay, 1 part of sodium gluconate, and 200 parts of water are stirred until mixed evenly, and then 100 parts of reinforcing fillers are added, mixed evenly, and naturally cured for 28 days to obtain high-strength energy-saving and emission-reducing recycled concrete.

[0089] Example 2

[0090] This embodiment provides a method for preparing high-strength energy-saving and emission-reducing recycled concrete, comprising the following steps:

[0091] S1, adding polyacrylamide and silicon carbide whiskers to silica sol in sequence, stirring and then adding magnesium oxide and steel fiber in sequence, wherein the mass ratio of silica sol, silicon carbide whiskers, magnesium oxide, steel fiber and polyacrylamide is 100:10:40:40:8, and then ball milling at a speed of 150 r / min for 30 min to obtain a reinforcing filler;

[0092] S2, 1000 parts of recycled coarse aggregate with a particle size of 10 mm, 490 parts of waste glass yarn with a particle size of 0.25 mm, 210 parts of waste marble with a particle size of 0.5 mm, 250 parts of ordinary Portland cement PO42.5, 10 parts of polycarboxylate water reducer, 10 parts of nanoclay, 1 part of sodium gluconate, and 200 parts of water are stirred until mixed evenly, and then 150 parts of reinforcing fillers are added, mixed evenly, and naturally cured for 28 days to obtain high-strength, energy-saving and emission-reducing recycled concrete.

[0093] Example 3

[0094] This embodiment provides a method for preparing high-strength energy-saving and emission-reducing recycled concrete, comprising the following steps:

[0095] S1, adding polyacrylamide and silicon carbide whiskers to silica sol in sequence, stirring and then adding magnesium oxide and steel fiber in sequence, wherein the mass ratio of silica sol, silicon carbide whiskers, magnesium oxide, steel fiber and polyacrylamide is 100:10:40:40:8, and then ball milling at a speed of 150 r / min for 30 min to obtain a reinforcing filler;

[0096] S2, 1000 parts of recycled coarse aggregate with a particle size of 10 mm, 490 parts of waste glass yarn with a particle size of 0.25 mm, 210 parts of waste marble with a particle size of 0.5 mm, 250 parts of ordinary Portland cement PO42.5, 10 parts of polycarboxylate water reducer, 10 parts of nanoclay, 1 part of sodium gluconate, and 200 parts of water are stirred until mixed evenly, and then 50 parts of reinforcing fillers are added, mixed evenly, and naturally cured for 28 days to obtain high-strength, energy-saving and emission-reducing recycled concrete.

[0097] Comparative Example 1

[0098] This comparative example provides a method for preparing high-strength energy-saving and emission-reducing recycled concrete, comprising the following steps:

[0099] S1, adding silicon carbide whiskers to silica sol in sequence, stirring and then adding magnesium oxide and steel fiber in sequence, wherein the mass ratio of silica sol, silicon carbide whiskers, magnesium oxide and steel fiber is 100:10:40:40, and then ball milling at a speed of 150 r / min for 30 min to obtain a reinforcing filler;

[0100] S2, 1000 parts of recycled coarse aggregate with a particle size of 10 mm, 490 parts of waste glass yarn with a particle size of 0.25 mm, 210 parts of waste marble with a particle size of 0.5 mm, 250 parts of ordinary Portland cement PO42.5, 10 parts of polycarboxylate water reducer, 10 parts of nanoclay, 1 part of sodium gluconate, and 200 parts of water are stirred until mixed evenly, and then 50 parts of reinforcing fillers are added, mixed evenly, and naturally cured for 28 days to obtain high-strength, energy-saving and emission-reducing recycled concrete.

[0101] Comparative Example 2

[0102] This comparative example provides a method for preparing high-strength energy-saving and emission-reducing recycled concrete, comprising the following steps:

[0103] S1, adding polyacrylamide and silicon carbide whiskers to silica sol in sequence, stirring and adding steel fiber, wherein the mass ratio of silica sol, silicon carbide whiskers, steel fiber and polyacrylamide is 100:10:40:8, and then ball milling at a speed of 150 r / min for 30 minutes to obtain a reinforcing filler;

[0104] S2, 1000 parts of recycled coarse aggregate with a particle size of 10 mm, 490 parts of waste glass yarn with a particle size of 0.25 mm, 210 parts of waste marble with a particle size of 0.5 mm, 250 parts of ordinary Portland cement PO42.5, 10 parts of polycarboxylate water reducer, 10 parts of nanoclay, 1 part of sodium gluconate, and 200 parts of water are stirred until mixed evenly, and then 50 parts of reinforcing fillers are added, mixed evenly, and naturally cured for 28 days to obtain high-strength, energy-saving and emission-reducing recycled concrete.

[0105] Comparative Example 3

[0106] This comparative example provides a method for preparing high-strength energy-saving and emission-reducing recycled concrete, comprising the following steps:

[0107] S1, adding magnesium oxide and steel fiber to silica sol in sequence, wherein the mass ratio of silica sol, magnesium oxide and steel fiber is 100:40:40, and then ball milling at a speed of 150 r / min for 30 min to obtain a reinforcing filler;

[0108] S2, 1000 parts of recycled coarse aggregate with a particle size of 10 mm, 490 parts of waste glass yarn with a particle size of 0.25 mm, 210 parts of waste marble with a particle size of 0.5 mm, 250 parts of ordinary Portland cement PO42.5, 10 parts of polycarboxylate water reducer, 10 parts of nanoclay, 1 part of sodium gluconate, and 200 parts of water are stirred until mixed evenly, and then 100 parts of reinforcing fillers are added, mixed evenly, and naturally cured for 28 days to obtain high-strength energy-saving and emission-reducing recycled concrete.

[0109] Comparative Example 4

[0110] Compared with Example 1, most of the steps are the same except that step S1 is not performed and reinforcing fillers are not added in step S2.

[0111] Test Case

[0112] The compressive strength and flexural strength of the concrete samples obtained in Examples 1 to 3 and Comparative Examples 1 to 4 were tested in accordance with GB / T 50081-2019, and the results are shown in Table 1 below.

[0113] Table 1 Mechanical properties of Examples 1 to 3 and Comparative Examples 1 to 3

[0114] Compressive strength(Mpa) Flexural strength(Mpa) Example 1 51.1 9.8 Example 2 54.6 10.8 Example 3 48.8 9.5 Comparative Example 1 25.4 5.2 Comparative Example 2 28.9 6.1 Comparative Example 3 23.1 4.8 Comparative Example 4 17.6 3.1

[0115] It can be seen from Table 1 above that the compressive strength of the concrete obtained in the embodiment of the present application can reach 54..6 MPa, and the flexural strength can reach 10.8 MPa, which are much higher than the concrete obtained in the comparative example, indicating that the present invention can effectively improve the compressive strength and flexural strength of concrete.

[0116] As shown in Comparative Example 1, when polyacrylamide is not added, silicon carbide whiskers cannot be evenly dispersed in the silica sol and are easy to agglomerate in the concrete. Magnesium oxide combined with silicon carbide whiskers by bonding is also easy to agglomerate, and the resulting concrete has uneven internal pores and poor mechanical properties.

[0117] As shown in Comparative Example 2, when magnesium oxide is not added, the mechanical properties of ordinary concrete cannot be achieved by relying solely on the gap filling effect of silicon carbide whiskers.

[0118] As shown in Comparative Example 3, when silicon carbide whiskers are not added, the mechanical properties of ordinary concrete cannot be achieved by relying solely on the curing effect of magnesium oxide.

[0119] As shown in Comparative Example 4, when no reinforcing filler is added, the mechanical properties of the concrete are significantly reduced.

[0120] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.

Claims

1. A high-strength energy-saving and emission-reducing recycled concrete, characterized in that: The composition comprises the following components by weight: 1000 parts of recycled coarse aggregate, 600-800 parts of recycled fine aggregate, 200-400 parts of cement, 50-200 parts of reinforcing filler, 0.5-20 parts of water reducer, 0.5-20 parts of thickener, 0-2 parts of retarder, and 150-250 parts of water; The recycled coarse aggregate is made from waste concrete through the steps of cleaning, crushing and sorting; The recycled fine aggregate is composed of waste glass yarn and waste marble in a mass ratio of (50-70): (30-50); The reinforcing filler is prepared in the following manner: Polyacrylamide and silicon carbide whiskers are sequentially added to the silica sol, and magnesium oxide and steel fiber are sequentially added after stirring, and the reinforcing filler is obtained after ball milling.

2. The high-strength energy-saving and emission-reducing recycled concrete according to claim 1, characterized in that: The mass ratio of the silica sol, silicon carbide whisker, magnesium oxide, steel fiber and polyacrylamide is 100:(5-15):(30-50):(30-50)(5-10); And / or, the stirring time is 4-8h; And / or, the ball milling time is 15-45 min, and the ball milling speed is 100-200 r / min; And / or, the length of the silicon carbide whisker is 10-50 μm, the diameter is 0.1-0.6 μm, and the particle size of the magnesium oxide is 50-100 nm.

3. The high-strength energy-saving and emission-reducing recycled concrete according to claim 1, characterized in that: The particle size of the recycled coarse aggregate is 5-10 mm, and the particle size of the recycled fine aggregate is 0.25-0.5 mm.

4. The high-strength energy-saving and emission-reducing recycled concrete according to claim 1, characterized in that: The water reducer is a polycarboxylate water reducer; And / or, the thickener is nanoclay; and / or, the retarder is one or more of sodium gluconate, citric acid, or sodium citrate; And / or, the cement is ordinary Portland cement PO42.

5.

5. A method for preparing high-strength energy-saving and emission-reducing recycled concrete, characterized in that: The following steps are involved: S1, adding polyacrylamide and silicon carbide whiskers to silica sol in sequence, adding magnesium oxide and steel fiber in sequence after stirring, and obtaining reinforcing filler after ball milling; S2, mixing recycled coarse aggregate, recycled fine aggregate, cement, water reducer, thickener, retarder and water until they are evenly mixed, then adding reinforcing filler, mixing evenly, and naturally curing to obtain high-strength energy-saving and emission-reducing recycled concrete; Wherein, the recycled coarse aggregate is made from waste concrete through the steps of cleaning, crushing and sorting; The recycled fine aggregate consists of waste glass yarn and waste marble in a mass ratio of (50-70):(30-50).

6. The method for preparing high-strength energy-saving and emission-reducing recycled concrete according to claim 4, characterized in that: In step S1, the mass ratio of the silica sol, silicon carbide whiskers, magnesium oxide, steel fiber and polyacrylamide is 100:(5-15):(30-50):(30-50)(5-10); And / or, in step S1, the stirring time is 4-8h; And / or, in step S1, the ball milling time is 15-45 min, and the ball milling speed is 100-200 r / min; And / or, in step S1, the length of the silicon carbide whisker is 10-50 μm, the diameter is 0.1-0.6 μm, and the particle size of the magnesium oxide is 50-100 nm.

7. The method for preparing high-strength energy-saving and emission-reducing recycled concrete according to claim 4, characterized in that: The mass ratio of the recycled coarse aggregate, recycled fine aggregate, cement, reinforcing filler, water reducer, thickener, retarder and water is 1000:(600-800):(200-400):(50-200):(0.5-20):(0-2):(150-250).

8. The method for preparing high-strength energy-saving and emission-reducing recycled concrete according to claim 4, characterized in that: In step S2, the particle size of the recycled coarse aggregate is 5-10 mm, and the particle size of the recycled fine aggregate is 0.25-0.5 mm.

9. The method for preparing high-strength energy-saving and emission-reducing recycled concrete according to claim 4, characterized in that: In step S2, the water reducer is a polycarboxylate water reducer; And / or, in step S2, the thickener is nanoclay; And / or, in step S2, the retarder is one or more of sodium gluconate, citric acid, or sodium citrate; And / or, in step S2, the cement is ordinary Portland cement PO42.

5.

10. A recycled concrete obtained by the method for preparing high-strength energy-saving and emission-reducing recycled concrete as claimed in any one of claims 5 to 9.

Citation Information

Patent Citations

  • A type of concrete and its preparation method

    CN112811869B

  • Recycled concrete adulteration material, recycled concrete and preparation method of recycled concrete adulteration material

    CN117088630A